2008
DOI: 10.1002/eat.20528
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing eating disorders in adolescents: A comparison of the eating disorder examination and the development and well‐being assessment

Abstract: Objective: To compare the diagnostic properties of the Eating Disorder Examination (EDE) and the online version of the Development and Well-Being Assessment (DAWBA).Method: Fifty-Seven adolescents (mean age 15.7 years) who attended consecutive assessments at a specialist eating disorders clinic completed the DAWBA, the EDE, and a standard clinical assessment with a multidisciplinary team. Cohen's Kappas were used to make pairwise comparisons between the diagnoses generated by the three assessments.Results: Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
0
29
0
2
Order By: Relevance
“…Given the limitations of self-report, alternative perspectives provided by a second informant may be useful in identifying potentially vulnerable individuals who may not identify themselves as symptomatic, or for conceptualising an adolescent’s behaviour in different contexts. Indeed, there has been some support for the use of computerised diagnostic assessments such as the DAWBA that takes into consideration multiple informants’ reports to calculate the probability of a child/adolescent having an ED [34, 35]. However, a Swiss study of child and adolescent outpatients comparing the ICD-10 diagnoses provided by clinicians to those reached through expert review of DAWBA data revealed that although agreement between the DAWBA expert and clinician ratings was observed, this was largely driven by negative ratings of EDs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Given the limitations of self-report, alternative perspectives provided by a second informant may be useful in identifying potentially vulnerable individuals who may not identify themselves as symptomatic, or for conceptualising an adolescent’s behaviour in different contexts. Indeed, there has been some support for the use of computerised diagnostic assessments such as the DAWBA that takes into consideration multiple informants’ reports to calculate the probability of a child/adolescent having an ED [34, 35]. However, a Swiss study of child and adolescent outpatients comparing the ICD-10 diagnoses provided by clinicians to those reached through expert review of DAWBA data revealed that although agreement between the DAWBA expert and clinician ratings was observed, this was largely driven by negative ratings of EDs [36].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the EDE and CIA are less sensitive to the symptoms and impairment associated with restrictive EDs. There is some evidence that the EDE is insufficiently sensitive and fails to detect all cases of AN and EDNOS [35], especially for adolescent samples [39]. Previous work also suggests that EDE global scores are somewhat lower in AN than BN patient groups (M AN = 2.65, M BN = 3.07) [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition we defined two categories of OSFED-other: 1 and 2, the former being assigned to youth who did not meet criteria for all other disorders but reported ED behaviors ≥monthly; the latter to those who reported any ED behaviors at < monthly frequency (with shape and weight concern at 14 years). Given evidence that young people often deny AN symptoms (such as fear of fatness and restrictive eating), and that the use of parental report can overcome this 16 , parental report of AN symptoms on a validated instrument–Development and Wellbeing Assessment (DAWBA) 17 –at Wave 14+ and 16+ (see 18 for details) was used in addition to self-report to define AN.…”
Section: Methodsmentioning
confidence: 99%